Comparative Analysis of The Development of Chinese Language Teaching in Indonesia and Malaysia——Focusing on Bereday's Four Step Method of Comparative Education Research: 印尼的中文教学发展与马来西亚对比分析——以贝雷迪的比较教育研究四步法为主 - David Vincensius (Mandarinable: Journal of Chinese Studies, 2024)
At present, Chinese teaching as a second language is becoming more and more famous, especially in countries along the One Belt One Road. As part of the One Belt One Road, Indonesia and Malaysia are no exception. Indonesia and Malaysia are neighboring countries in Southeast Asia. The purpose of this study is to compare educational research, using Bereday's "Four Step Approach to Comparative Education Research" methodology, and using various literature to conduct literature research as support for the research. Research has shown that the development of Chinese language teaching in Indonesia is slightly slower than that in Malaysia, which is influenced by these three factors, learning content, government policies, and history.